2007
DOI: 10.1063/1.2793737
|View full text |Cite
|
Sign up to set email alerts
|

Fluid and kinetic parameters near the plasma-sheath boundary for finite Debye lengths

Abstract: In a recent paper by Kuhn et al. [Phys. Plasmas 13, 013503 (2006)], it has been demonstrated that in a plasma, the polytropic coefficient γ is a spatially varying quantity rather than a global constant as usually assumed in fluid theory. Assuming cold ion sources and using the asymptotic two-scale approximation (in which the ratio of the Debye length over the characteristic presheath length, ε, is set to zero), it was found that the γ profile exhibits a sharp peak (with values roughly between 6 and 8) at the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 41 publications
4
30
0
Order By: Relevance
“…Since the code BIT1 has the ability to maintain the prescribed electron temperature and the Maxwellian shape of the electron velocity distribution function, it is very suitable for this purpose. It has been shown that the results of this code are in very good agreement with the analytical solutions [11] of the TonksLangmuir model for the ions born at rest. The code could very probably also be used for the study of sheath formation in more fusion relevant conditions with warm ions [19][20][21] and magnetic field [22][23][24] present.…”
Section: Separate Tracking Of Reflected Electronssupporting
confidence: 62%
“…Since the code BIT1 has the ability to maintain the prescribed electron temperature and the Maxwellian shape of the electron velocity distribution function, it is very suitable for this purpose. It has been shown that the results of this code are in very good agreement with the analytical solutions [11] of the TonksLangmuir model for the ions born at rest. The code could very probably also be used for the study of sheath formation in more fusion relevant conditions with warm ions [19][20][21] and magnetic field [22][23][24] present.…”
Section: Separate Tracking Of Reflected Electronssupporting
confidence: 62%
“…The electron kinetic effects have a strong impact on the ion velocity, and the sheath-edge definition needs to be refined according to Eq. (7). This new definition of the sheath edge is coherent with the breaking of neutrality and other sheath-edge quantities and is valid for all η se > 0.…”
Section: Discussionmentioning
confidence: 86%
“…The condition of ambipolar flow i = e can be found by solving V i,se = V e,se , expressed by Eqs. (4) and (7). This defines the floating potential, which is found to be at η se ≈ for the hydrogen mass ratio (μ = 1836, 2.8) or higher.…”
Section: Derivation Of the Sheath-edge Locationmentioning
confidence: 99%
See 1 more Smart Citation
“…which validity has been further examined by Riemann 12 under particular discharge scenarios and further elaborated by Jelic et al 13 and Kuhn et al 14 Anyway, here we will remain within the framework of kinetic model. In Sec.…”
Section: Introductionmentioning
confidence: 98%